Penerapan Ecosystem-Based Management untuk Mendukung Budidaya Mutiara Berkelanjutan di Perairan Lombok Barat - Nestiyanto Hadi; Noverita Dian Takarina; Luthfiralda Sjahfirdi; Mufti Petala Patria (Fakultas Seni Rupa dan Desain ITB, 2026)
Lombok Island is a major center for the cultivation of the Pinctada maxima pearl oyster, a species renowned for producing high-value South Sea pearls. The sustainability of pearl farming in this region relies not only on favorable water quality but also on the effective implementation of Ecosystem-Based Management (EBM), which integrates the roles of government agencies, industry stakeholders, and local communities in safeguarding marine ecosystem integrity. This study applied an EBM approach to assess environmental suitability for sustainable pearl cultivation in West Lombok. Field data were collected from three cultivation sites between January and February 2025 through in situ measurements and laboratory analyses of key physicochemical parameters. The results show that pH (7.69), dissolved oxygen (6.38 mg/L), salinity (29.69‰), ammonia (0.037 mg/L), and TSS (0.065 mg/L) were within optimal ranges and complied with marine water quality standards. However, water temperatures reached up to 32.8°C at several sites, exceeding the optimal thermal range for Pinctada maxima and posing risks of physiological stress and reduced pearl quality. To mitigate temperature-related stress, flotation-controlled longline technology can be employed to adjust oyster depth in accordance with thermocline layers that provide more stable thermal and salinity conditions. The integration of such adaptive technologies—combined with active, multi-stakeholder collaboration under the EBM framework—constitutes a critical foundation for maintaining ecosystem stability and ensuring the long-term socioeconomic sustainability of the pearl farming sector in West Lombok.